SUSTAINABILITY OF VANAME SHRIMP (Litopenaeus vannamei) FARMING IN BANTAN DISTRICT BENGKALIS REGENCY, RIAU - Hutasuhut, Wilda Rizkiyah; Hendrik, Hendrik; Arief, Hazmi (Asian Journal of Aquatic Sciences, 2024)
Bantan district is one of the districts on the coast of Bengkalis Regency, which has great potential to contribute to vaname shrimp production through intensive technology pond-based farming activities. This study aims to assess the sustainability status of vaname shrimp farming in the Bantan District. The data processing and data analysis were performed using Multi-Dimensional Scaling (MDS); the ordination process is performed using the ordination technique called Rapid Appraisal for Shrimp Farm (Rap-SF), which is a modification of Rap-FISH Rapid Appraisal for fisheries (Rapfish) using five dimensions namely ecological, economic, social, institutional, and technological. The research results show the sustainability index of the ecological dimension with a value of 47.27 (less sustainable), the economic dimension with a value of 59.55 (quite sustainable), the social dimension 52.88 (quite sustainable), the institutional dimension 47.10 (less sustainable) and the technological dimension 63.35 (quite sustainable). Technological and economic dimensions have a considerable influence on the sustainability of vaname shrimp farming in the Bantan District